p53 Expression, Programmed Death Ligand 1, and Risk Factors in Urinary Tract Small Cell Carcinoma - Golijanin, Borivoj; Gershman, Boris; De Souza, Andre; Kott, Ohad; Carneiro, Benedito A.; Mega, Anthony; Golijanin, Dragan J.; Amin, Ali (Frontiers in Oncology, 2021)
Introduction Small cell carcinoma of the urinary tract (SCCUT) is a rare finding with poor clinical course. This study sheds light on the molecular subtype and identifies risk factors in patients diagnosed with SCCUT. Materials and Methods Immunohistochemical expression of immunotherapy target PD-L1, and luminal (GATA3), basal (p63), and p53 markers are assessed in patients diagnosed with SCCUT. Univariate analysis identified risk factors. Overall-survival (OS) is computed using the Kaplan-Meier method. Results Tissue was available for 70.2% (33/47). All showed a high PD-L1 expression phenotype. p53 is seen in 93.9% (31/33), mostly as overexpression, GATA3 in 45.5% (15/33), and p63 in 57.6% (19/33). For the entire cohort (n=47), one-year survival was 59.6% and the median OS was 17 months. Univariate analysis shows that chemotherapy (HR = 0.29, 95 % CI = 0.14 – 0.61, p=0.001), radical surgery (HR = 0.37, 95 % CI = 0.18 – 0.76, p=0.007), and diagnosis of non-pure SCCUT (HR = 0.44, 95 % CI = 0.22 – 0.86, p=0.02) are favorable prognostic features. Metastasis had negative associations with survival (HR = 2.1, 95 % CI = 1.1 – 4.2, p=0.03). Conclusions In this series, pure and mixed SCCUT are characterized by p53 overexpression and a high PD-L1 phenotype. Histology of non-pure SCCUT is a positive prognosticator, and radical cystectomy or chemotherapy can improve OS. These findings demonstrate that SCCUT may be eligible for PD-L1 immunotherapy.